PERANCANGAN APLIKASI UNTUK MONITORING PENJADWALAN, PERCETAKAN DAN PENERBITAN BUKU PADA PT. PENERBIT IPB PRESS BERBASIS WEB MENGGUNAKAN METODE WATERFALL - angga ramdani; Devi Yunita (CV. Multi Kreasi Media, 2022)
IPB Press Publisher is a company engaged in printing, publishing and procurement of books that still require expansion in this field, for the publication itself is still in a stage that is considered quite experienced, with more than 1500 book titles that have been published since 2009 the company was founded, will but for scheduling the printing of the book itself, it is still manual which takes quite a long time, thus allowing frequent occurrences of schedules that are not according to demand or ignorance of the account manager as the person who enters the schedule for the completion of the schedule. By building a book scheduling and monitoring system, it can help both account managers, supervisors, operators and writers to know which books have been processed until they are published. This system will be developed using the Waterfall method and implemented using UML (Unified Modeling Language), PHP and Mysql. The results of this study are in the form of designing a web-based book scheduling and monitoring system that can be implemented properly by the company in order to make it easier for users to work more optimally.